210Po microsphere radiological design for tumor vascular disruption - JJ Bevelacqua (PeerJ, 2015)
The feasibility of disrupting a tumor’s vascular structure using 210Po microspheres is investigated using standard ion and photon absorbed dose methodologies. Calculated absorbed dose profiles for 210Po alpha particles are sufficient to disrupt a tumor’s arteriole structure while minimizing the dose outside the blood vessel wall. 210Po photons contribute minimal dose to healthy tissue. The requisite activity of 210Po to facilitate vascular disruption is calculated.